2003
DOI: 10.1381/096089203321136566
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing Gastric Staple-Lines with Bovine Pericardial Strips May Decrease the Likelihood of Gastric Leak after Laparoscopic Roux-en-Y Gastric Bypass

Abstract: In this non-randomized trial, BPS were found to be easy and safe to use. In addition, staple-line hemorrhage was essentially non-existent. Although the reduction in gastric staple-line leak rate may also be attributed to learning curve, there were no acute leaks in 250 patients with BPS, which is below the published norms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 11 publications
1
48
2
Order By: Relevance
“…Peri-Strips Dry ® (Synovis, Saint Paul, MN) are composed of two strips of biological tissue derived from bovine pericardium that are applied to the linear stapler and act as a buttressing material at the staple-lines. 9,10 Seamguard ® (W. L. Gore & Associates, Flagstaff, AZ) staple-line reinforcement works in a similar fashion using ePTFE instead of biologic tissue. De la Torre and colleagues 11 reported the use of Seamguard ® on 50 laparoscopic RYGBP patients; they did not find any postoperative GI hemorrhages in their study.…”
Section: Preventionmentioning
confidence: 99%
“…Peri-Strips Dry ® (Synovis, Saint Paul, MN) are composed of two strips of biological tissue derived from bovine pericardium that are applied to the linear stapler and act as a buttressing material at the staple-lines. 9,10 Seamguard ® (W. L. Gore & Associates, Flagstaff, AZ) staple-line reinforcement works in a similar fashion using ePTFE instead of biologic tissue. De la Torre and colleagues 11 reported the use of Seamguard ® on 50 laparoscopic RYGBP patients; they did not find any postoperative GI hemorrhages in their study.…”
Section: Preventionmentioning
confidence: 99%
“…Examples of clinically available buttress reinforcement materials are bovine pericardium (Peri-strips ® ), [15][16][17][18][19] expanded-polytetrafluoroethylene (ePTFE ® ), 18,20 polyglycolic acid (PGA)-trimethylene carbonate (TMC) copolymer (Gore Seamgaurd ® ) 21,22 and small intestinal submucosa (Surgisis ® ) [23][24][25][26] . These products have demonstrated some success in reducing leakage and bleeding complications associated with staple lines.…”
Section: Introductionmentioning
confidence: 99%
“…The two studies investigating this technique showed positive results regarding leakage and bleeding [34, 35] which were markedly reduced.…”
Section: Staple Line Reinforcementmentioning
confidence: 99%
“…In addition to pulmonary resections, bovine pericardium staple line reinforcement has proven to be successful in bariatric procedures in several studies [34, 35]. During laparoscopic Roux-en-Y gastric bypasses, blood loss was significantly decreased or even absent, thereby improving the visibility with fewer conversions and reduced operating time.…”
Section: Experiences With Staple Line Reinforcementmentioning
confidence: 99%